PENGARUH LINGKUNGAN KELUARGA DAN MINAT MEMBACA TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS XI ILMU PENGETAHUAN SOSIAL SEKOLAH MENENGAH ATAS NEGERI KOTA PADANG - Welven Aida (Jurnal Ilmiah Cano Ekonomos, 2015)
The purpose of this research was to know and analyze: (1) The influence of familyenvironment on students'interest in reading class XI IS high schools in the city of Padang(2) The influence of family environment and interest in reading for class XI student learningresult IS high schools in the city of Padang. This kind of this research belong to thecausative descriptive study with a population of 1,779 students. The sampling techniqueused a Proportional Stratified Random Sampling taken based on school accreditation. Thesample totaled 327 students taken from theen tire population. The primary data in this studywere obtained from question naires that were distributed to the respondents, whilesecondary data was data associated with the objectsof the research presented by otherparties, namely student learning outcomes data fromthe value of the End SemesterExamination (UAS) of Economics subjects. Data analysis techniques used by using pathanalysis with SPSS version 15.00. To examine the hypothesis used the F test and t test. Theresults of this research ere: (1) There isa significant effect of family environment onstudents'interest in reading class XI IS SMA Negeri Padang (2) There is a significant effectof family environment and interest in reading for class XI student learning result of IS classon SMA Negeri Padang. Adviceto parents to pay attention to the environmental aspects offamily and children in order to increase interest in reading learning result are achieved forthe better.